2020
DOI: 10.1093/nar/gkaa034
|View full text |Cite
|
Sign up to set email alerts
|

ADAPT identifies an ESCRT complex composition that discriminates VCaP from LNCaP prostate cancer cell exosomes

Abstract: Libraries of single-stranded oligodeoxynucleotides (ssODNs) can be enriched for sequences that specifically bind molecules on naïve complex biological samples like cells or tissues. Depending on the enrichment strategy, the ssODNs can identify molecules specifically associated with a defined biological condition, for example a pathological phenotype, and thus are potentially useful for biomarker discovery. We performed ADAPT, a variant of SELEX, on exosomes secreted by VCaP prostate cancer cells. A library of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…In different cellular contexts, caveolin‐1 was shown as a direct interactor of hnRNPA2B1 (Lee et al., 2019), while Rab27a was found modulated by hnRNPH1 (Datta et al., 2017), and hnRNPK directly involved in LC3‐depended EV loading and secretion (Leidal et al., 2020). Relevantly, other RBPs, such as YBX1 and MEX3C, were found in complex with central nodes of the ESCRT machinery (Hornung et al., 2020) or clathrin‐mediated endocytosis (Lu et al., 2017), respectively, underlying the existence of a significant role in the transport of, at least sub‐populations, of vesicles. These relationships gain mechanistic values when specific PTMs are associated with a cytoplasmic activity of the RBP and the EV‐RNA results consequently modulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In different cellular contexts, caveolin‐1 was shown as a direct interactor of hnRNPA2B1 (Lee et al., 2019), while Rab27a was found modulated by hnRNPH1 (Datta et al., 2017), and hnRNPK directly involved in LC3‐depended EV loading and secretion (Leidal et al., 2020). Relevantly, other RBPs, such as YBX1 and MEX3C, were found in complex with central nodes of the ESCRT machinery (Hornung et al., 2020) or clathrin‐mediated endocytosis (Lu et al., 2017), respectively, underlying the existence of a significant role in the transport of, at least sub‐populations, of vesicles. These relationships gain mechanistic values when specific PTMs are associated with a cytoplasmic activity of the RBP and the EV‐RNA results consequently modulated.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, using an easily detectable sequence as a probe for target capturing, the authors identified proteins known to be involved in the formation of the endosomal sorting complexes required for transport (ESCRT) machinery. In these settings, YBX1 was identified as part of this interactome, specifically in complex with ubiquitinylated TSG101 (Hornung et al., 2020).…”
Section: Ybx1mentioning
confidence: 99%
“…Less complex (i.e. focused more strictly) libraries have been used in the context of cancer diagnostics in a way that mixtures of up to 2000 synthetic individual aptamers were used to create functional polyclonality [9–11] . Inspired by the FluMag‐SELEX, [12] evolution of aptamers was followed by Cyanine 5 (Cy5) labelling of the aptamers and analysis of binding to whole cells as separable particles, a procedure we consequently decided to name the “FluCell‐SELEX”.…”
Section: Methodsmentioning
confidence: 99%
“…focusedm ore strictly) libraries have been used in the context of cancer diagnostics in aw ay that mixtures of up to 2000 synthetic individual aptamers were used to create functional polyclonality. [9][10][11] Inspired by the FluMag-SELEX, [12] evolution of aptamers was followed by Cyanine 5( Cy5) labelling of the aptamers and analysiso fb inding to whole cells as separable particles, ap rocedure we consequently decided to name the "FluCell-SELEX". Moreover,i tw as demonstrated that in contrast to single aptamers the library influenced virulence relevant cell functions anda llowed the affinity based isolation and subsequentp roteomici dentification of bound prominent outer membrane proteins as targeted cell surfacestructures.…”
mentioning
confidence: 99%
“…Recently, we have shown that reliable molecular diagnostic of the human pathogen P. aeruginosa can be conducted simply by using a focused polyclonal aptamer library, as it results from the SELEX process without the need to identify and characterize individual sequences to generate defined single affinity molecules. However, this concept to use a polyclonal library was shown to require sophisticated biotechnological production strategies, allowing the long-term maintenance of the diversity (i.e., the available functional sequence space) in the library composition [ 26 , 35 , 39 , 40 ]. The polyclonal library after 13 rounds of selection against A. muciniphila was similarly well suited and allowed to specifically label and distinguish Akkermansia cells from other gut bacterial, which served as controls in a minimal model gut microbiome in our experiments.…”
Section: Discussionmentioning
confidence: 99%